Remotely-driven management of diuretic therapy in heart failure patients with a multiparametric ICD algorithm. (19th May 2022) - Guerra, F; D'onofrio, A; De Ruvo, E; Manzo, M; Santini, L; Giubliato, G; La Greca, C; Petracci, B; Stronati, G; Bianchi, V; Martino, A; Franculli, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Boston Scientific Background: HeartLogic algorithm combines data from multiple sensors to predict future heart failure (HF) decompensation in patients with an implantable defibrillator (ICD) . An optimal strategy to manage algorithm alerts is not yet known, although decongestive treatment with diuretics is the most frequent alert-triggered action reported so far. Purpose: We describe the implementation of HeartLogic for remote monitoring of HF patients, and we evaluate the approach to diuretic dosing and timing of the intervention in patients with device alerts. Methods: The study was conducted in eight Italian high-volume arrhythmia centers. The algorithm was activated in 229 ICD patients during a median follow-up was 17 months [25th–75th percentile: 11-24] between December 2017 and July 2020. Remote data reviews and patient phone contacts were undertaken at the time of HeartLogic alerts, to assess the patient's status and to prevent HF worsening. The study protocol did not mandate any specific intervention algorithm, and physicians were free to remotely implement clinical actions, to schedule extra in-office visits when deemed necessary for additional investigations or for interventions, or to adopt an active monitoring approach. We analyzed alert-triggered augmented HF treatments, consisting of isolated increases in diuretics dosage. Results: We reported 242 alerts (0.8 alerts/patient-year) in 123 patients, 137 (56%) alerts triggered clinical actions to treat HF. Overall, timely diuretic changes were associated with a shorter "in-alert" state duration in comparison with late changes, i.e. 28 days [25th-75th percentile: 20-43] versus 62 days [25th-75th percentile: 44-118], p<0.001. By contrast, major and minor diuretic augmentations resulted in comparable durations, i.e. 47 days [25th-75th percentile: 30-58] versus 38 days [25th-75th percentile: 23-79], p=0.954. Of the 56 decongestive treatment adjustments, 47 resolved the alert condition, while in the remaining 9 cases, further treatments were required (augmented HF therapy during hospitalization or unscheduled intravenous decongestive therapy in outpatients). The need of hospitalization for further treatments to resolve the alert condition was associated with higher HeartLogic index values on the day of the diuretics increase (odds ratio: 1.11, 95%CI: 1.02-1.20, p=0.013) and with late interventions (odds ratio: 5.11, 95%CI: 1.09-24.48, p=0.041). No complications were reported after drug adjustments. Conclusions: Decongestive treatment adjustments triggered by HeartLogic alerts, even when such adjustments were completely dependent on the physicians' clinical expertise and were not standardized. The early use of decongestive treatment and the use of high doses of diuretics seem to be associated with more favorable outcomes.